Far from the Madding Crowd - Hardy, Thomas, 1840-1928 (Salt Lake City, UT : Project Gutenberg, 1994)
"Far from the Madding Crowd" by Thomas Hardy is a novel published in 1874. It follows the independent Bathsheba Everdene, who inherits a farm in rural England and attracts three very different suitors: the faithful shepherd Gabriel Oak, the obsessive gentleman farmer William Boldwood, and the dashing but reckless Sergeant Frank Troy. Set against the backdrop of Victorian farming life, this tale of love, honor, and betrayal explores the consequences of impulsive choices and the complexity of the human heart. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Far_from_the_Madding_Crowd
Release date is 1994-02-01
anonymous Project Gutenberg volunteers and revised by Joseph E. Loewenstein, M.D.
Keywords: Didactic fiction; Love stories; Triangles (Interpersonal relations) -- Fiction; Pastoral fiction; Farm life -- Fiction; Women farmers -- Fiction; Wessex (England) -- Fiction